GAMIFIKASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN CAPAIAN BELAJAR DI SEKOLAH BERBASIS PESANTREN - Sabrina Putri; Ainul Yaqin; Hajar Nurma Wachidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The advancement of technology in education has encouraged teachers to implement more innovative learning strategies to create active and meaningful learning experiences. One strategy that can be applied in Islamic Religious Education (IRE) learning is gamification. This study aims to analyze the implementation of gamification in Islamic Religious Education learning and its relationship with students' learning outcomes at SMA Darul Qur'an Mojokerto. This study employed a qualitative approach with a case study design. Data were collected through observations, interviews with an Islamic Religious Education teacher and tenth-grade students, as well as documentation. Data were analyzed using data condensation, data display, and conclusion drawing, while data credibility was ensured through source, technique, and time triangulation. The findings indicate that gamification was implemented systematically through the stages of planning, implementation, evaluation, and reflection. The teacher utilized various digital platforms, including Quizizz, Kahoot, Wayground, and Quizlet, by integrating gamification elements such as points, badges, levels, and immediate feedback to enhance students' engagement. The implementation contributed to students' learning outcomes, particularly in the cognitive domain through improved understanding of the learning materials and in the affective domain through increased enthusiasm, participation, and learning motivation. Therefore, gamification can serve as an effective instructional strategy to promote more interactive, meaningful, and student-centered learning in Islamic Religious Education.